FRAUDULENT FINANCIAL REPORTING BY DISTRICT / MUNICIPAL GOVERNMENT IN INDONESIA1 - Indra Kusuma; Halim Dedy Perdana; Sri Suranta (Asia Pacific Fraud Journal, 2017)
ABSTRACTThis research aims to analyze and obtain empirical evidence about the influence of fraud diamond (pressure, opportunity, rationalization, and capability) on fraudulent financial reporting in the public sector. Opinion on the financial statements of the district / municipal government in Indonesia is used as a proxy to indicate fraudulent financial reporting. The population used in this research is the district / municipal governments in Indonesia. The total samples are 437 district / municipal governments obtained through convenience sampling method. This research uses secondary data drawn from BPK’s Audit Reports of 2014 and 2015 and BPK’s Audit Results Summary of the First Semester (IHPS) of 2015. To analyze the data, this research uses logistic regression analysis with the SPSS 20.0 software tools. The results show that the factor of pressure, ie financial target that is proxied by percentage of budget realization has negative effect on fraudulent financial reporting; the factor of opportunity, ie related party transaction that is proxied by income transfers from the central government and internal control weakness that is proxied by audit findings of internal control systems in BPK’s Audit Result Reports has positive effect on fraudulent financial reporting, ie the factor of capability that is proxied by changes of regent / mayor has positive effect on fraudulent financial reporting, while the factor of pressure, ie external pressure that is proxied by local government capability of paying its liabilities (leverage) and the factor of rationalization that is proxied by previous year non-unqualified opinion has no significant effect on fraudulent financial reporting.